Design of Bi-directional DC-DC Converter for 10 kVA Virtual Synchronous Motor - LYU Zhipeng; LU Guotao; LIU Lan; QIU Lijun (机车电传动)
Virtual synchronous motor is composed by inverter, DC converter and system power supply. Once paralleled with the power grid, VSM could either send or absorb power, energy bi-directional flow was required in the design of DC converter. A bi-directional DC converter design scheme was provided with two series IGBT and a boost inductance in series on the neutral line of the low voltage side. The test shows that the scheme can achieve the boost and buck switching actively, energy bi-directional flow and the intermediate DC voltage stabilization. This design has the advantage of the simple control method, high precision voltage regulation, can met the voltage regulation and energy storage requirements of the new 10 kVA virtual synchronous motor.